Gain calibration of the ALICE TRD using the decay of 83mKr by internalconversion - Stiller, Johannes Hendrik (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2013)
For an early calibration of the ALICE TRD on the level of individual readout pads a dedicated calibration run with a Krypton source was carried out. We recorded 2.28×109 decays of metastable 83mKr in the 6.46×105 readout-pads of the 10 TRD super modules presently installed in the ALICE experiment [1] at CERN. In our analysis the gain uniformity within each chamber as well as the energy resolution of all installed chambers were obtained. This is crucial for good online particle identification and thus triggering. In an iterative analysis step, these gain factors converged to 1% gain uniformity at the readout pad level. Additionally, a comparison between the obtained results and corresponding findings from measurements during chamber construction was performed and good agreement was found. The pad gain factors are uploaded into the front-end electronics for online gain correction to ensure stable trigger conditions.
Available online 14 May 2012
Im Titel ist "83m" bei Kr hochgestellt
Gesehen am 22.02.2022